Peran Good Corporate Governance dalam Hubungan Family Involvement dan Nilai Perusahaan - Pramurindra, Rezky; Pretisila Kartika Putri; Irham Muhammad Azama (ITB AAS Indonesia Surakarta, 2025)
The risk of rising inflation, the prospect of high interest rates, escalating trade and geopolitical tensions have left the global economy in a state of ongoing uncertainty. The high prevalence and market valuation of companies with family involvement make this form of business organization an important component in the global capital market. How can family businesses maintain and increase company value amidst global economic uncertainty? This study aims to examine the causal relationship between family involvement and company value with good corporate governance as a moderating variable. The study population is all property and real estate sector companies listed on the Indonesia Stock Exchange for the period 2021-2024. Hypothesis testing using SPSS results in: (1) Family Involvement has a positive and significant effect on company value, (2) Institutional Ownership strengthens the influence of family involvement on company value, (3) An independent board of commissioners strengthens the influence of family involvement on company value, (4) The audit committee does not moderate the influence of family involvement on company value. Mitigating agency problems and implementing good corporate governance can encourage companies to achieve better financial performance, so that the company can continue from one generation to the next.